2021
DOI: 10.1017/s0963548321000067
|View full text |Cite
|
Sign up to set email alerts
|

Powers of paths in tournaments

Abstract: In this short note we prove that every tournament contains the k-th power of a directed path of linear length. This improves upon recent results of Yuster and of Girão. We also give a complete solution for this problem when k=2, showing that there is always a square of a directed path of length , which is best possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3
1

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…He showed that any tournament on n vertices must contain a power of a directed path on at least n 0.295 vertices. Confirming a conjecture of Yuster, Draganić et al [5] showed that for every k there always exists a k-th power of a path of linear order. Theorem 1.1 (Draganić et al [5]).…”
Section: Introductionmentioning
confidence: 71%
“…He showed that any tournament on n vertices must contain a power of a directed path on at least n 0.295 vertices. Confirming a conjecture of Yuster, Draganić et al [5] showed that for every k there always exists a k-th power of a path of linear order. Theorem 1.1 (Draganić et al [5]).…”
Section: Introductionmentioning
confidence: 71%
“…Previous work showing linear upper bounds on − → r 1 (H) when H is an oriented tree (e.g. [14]) or an acyclic digraph of bounded bandwidth [12] all depend on embedding H into a tournament T in some iterative manner according to its median ordering. We were not able to reproduce these upper bounds using greedy embedding arguments, which seem primarily suited for embedding digraphs H without long paths.…”
Section: − → G (N D) Andmentioning
confidence: 99%
“…Using the same argument, one can obtain a bound of − → r 1 (H) ≤ n O ℓ (1) for any n-vertex acyclic digraph of bandwidth at most ℓ, using the fact that the same binary-representation prefix coloring have dyadic complexity at most n O(log ℓ) . However, since the Ramsey number of bounded-bandwidth acyclic digraphs is known to be linear [12], we omit the proof of this weaker result.…”
Section: Upper Bounds For Random Digraphsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to find this partition into chains we use the recent result in [6], which shows that one can always find the k-th power of a long path in a tournament. We apply this iteratively, until a certain constant number of vertices is left.…”
Section: Cut-dense Tournamentsmentioning
confidence: 99%